Identification of Genes in Positive Alleles Marking Type II Diabetes Mellitus Using Primer D20: Identifikasi Gen pada Alel Positif Penanda Diabetes Melitus Tipe II Menggunakan Primer D20 - Kartikasari, Erina Wahyu; Mushlih, Miftahul (Universitas Muhammadiyah Sidoarjo, 2021)
Diabetes Mellitus is a metabolic disorder disease characterized by an increase in blood glucose due to insulin resistance (impaired insulin function) and or a decrease in insulin secretion. Genetically, Type 2 Diabetes Mellitus is influenced by genes that affect glucose metabolism in the body. The purpose of this study was to identify the genes involved in type 2 diabetes mellitus patients who were amplified using D20 primers. The method used in this research is descriptive experimental using 2 whole blood samples and 8 samples collected from DNA isolation in the Molecular Biology Laboratory of Type 2 Diabetes Mellitus patients. The results of the research based on the BLAST program obtained matched gene sequences from the sequenced leucine rich repeats gene. and guanylate kinase domain containing (LRGUK). The LRGUK gene is thought to be associated with Type 2 Diabetes Mellitus because the presence of SNP (Single Nucleotide Polymorphism) in the area around the LRGUK gene (7q32) shows a significant relationship with fasting blood glucose.